Decarbonizing Development : Green and Sustainable Bonds in Mitigating Emissions in Asian Countries - Mahajan, Anshul; Pathak, Rasna (Indian Journal of Finance, 2025)
Purpose : Environmental concerns gained prominence in the last century due to industrialization's rapid rise of the world economy. The rise of the GSB market was widely regarded as a positive development in the ongoing battle against climate change. This research paper examined the general effect of GSBs on sustainability, particularly in developing nations. Methodology : The study selected a sample of 16 emerging Asian-Pacific countries between 2015 and 2022 to look into the total influence of GSBs on CO2 emissions together, with GSBs on the production of RE, using STATA. This paper utilized secondary data to look at the existing CO2 emissions scenarios and GBs. We also used the panel data with a robust fixed-effect regression model. Findings : We found that CO2 emissions had somewhat dropped with GSBs moving upward annually on a global scale; whereas, global CO2 emissions were negatively affected by GSBs. Additionally, GSBs had a positive effect on RE production in Asian countries, with RE production positively impacting carbon emissions. Practical Implications : It was recommended that practitioners and decision-makers in the domains of environmental policy need to consider their impact on carbon emissions through various government policies, which have the potential to completely transform environmental laws and regulations. Our study is not free from limitations and allows scope for future researchers. Originality : Unlike prior research on GSB, the current work examined the overall impact of green and sustainable bond issuance on the overall sustainability at a global level.